THE CHANGING FACE OF NUTRITION AND DIETETICS IN JORDAN - Ahmad, Mousa Numan (European Scientific Journal, ESJ, 2014)
This article describes and examines the elements and indicators of health, nutrition and dietetics transition in Jordan over the past three decades. The picture of dietetics and hospital foodservice in Jordan has changed drastically along with remarkable transition in nutritional and health status accompanied by very rapid dietary, socioeconomic, epidemiologic and demographic shifts. Accelerated changes have occurred in trends of general health and nutritional status including decline in infectious diseases, increased life expectancy, rise in urbanization, mechanization and market globalization, decreased physical activity, diets have become sweeter, energy- and fat-dense and rich in animal foods. Concordant troubling trends have been recorded for rise in morbidity and mortality of major diet-related chronic disorders, particularly diabetes, cardiovascular diseases, obesity and cancer. In contrast to this transition, the patterns of dietetics and hospital foodservice have changed at a slow but steady pace. Dietetics profession has gained some official recognition and legal status permitting certification or licensing and consultation and private practice, though this progress has been hindered by poor legislative and regulatory attributes and lack of internship and in-service training programs and national traditional diet manuals. This has greatly hindered the dietetics professionalization process and lead to fall short of international guidelines. Thus, dietitians have not attained suitable place in nutritional care process as their tasks have not been adequately set up, resulting in lack of harmonious relations between physicians and dietitians, a major deterrents to dietitians’ performance. The need for dietetics organization is recognized in order to shape the profession’s face to international standards.